Analysis of the Development of the Electromobility Market in Poland in the Context of the Implemented Subsidies - Ewelina Sendek-Matysiak; Zbigniew Łosiewicz (Energies, 2021)
The flagship project in this area in Poland is the Electromobility Development Program, one of the strategic documents of which is the Act on Electromobility and Alternative Fuels of 11 January 2018, which includes a system of benefits aimed at influencing consumer behaviors towards the choice of electric vehicles. According to the decision-makers, its implementation is expected to result in the achievement of a number of goals, among others, 1 million of such vehicles are forecast to be present at the national level in 2025. The intention of the authors is to analyze the progress in the development of electromobility in Poland, in the areas such as the market of electric cars, charging infrastructure, with an indication of whether the actions that are implemented by the legislator, i.e., guidelines on where and in what quantities charging stations dedicated to such vehicles are to be established, subsidies in the form of the possibility of driving on the lanes designed for buses, subsidies for the purchase of such vehicles intensify the development of electromobility in the country. The considerations were carried out for cars powered exclusively by electricity, i.e., BEV (Battery Electric Vehicle) type, category M1. Cars in this category represent the largest share of the automotive market in Poland—over 75%. The utilitarian value of this research may be supported by the fact that the example of Poland and its problems concerning the discussed issue may be a source of preliminary analysis for other countries of the European Union.